Antioxidant Activity Test of Extract Fruit (Annona Squamosa L.) Young and Mature with FRAP Method (Ferric Reducing Antioxidant Power) - Wahyudi, Haekal; Adlim; M. Nasir (Al-Kimia, 2022)
The antioxidant activity test of young and ripe Srikaya fruit extract (Annona Squamosa L.) had been carried out by using the FRAP (Ferric Reducing Antioxidant Power) method. This study aims to determine the antioxidant activity of young and ripe srikaya fruit extract using the FRAP method by using qualitative and quantitative method. The research method used was FRAP (Ferric Reducing Antioxidant Power) which was based on a reduction reaction in an acid state towards a yellow Fe3+ (Potassium hexacyanoferat(III)) complex compound to become a bluish-green Fe2+ complex compound due to electron donors from antioxidant compounds. The result of the qualitative analysis of the antioxidant activity of young and ripe srikaya fruit extract was a change in color in the sample extracts of young and ripe Srikaya fruit due to the reduction reaction in an acid state towards the yellow-colored Fe3+ (Potassium hexacyanoferat(III)) complex compound to become a bluish-green Fe2+ complex compound. due to electron donor of antioxidant compounds. Quantitatively, the average antioxidant activity of samples of young and ripe srikaya fruit extract was respectively 7,448 mgAAE/g extract and 9,351 mgAAE/g extract. The result indicated that the antioxidant activity of ripe srikaya fruit was greater than that of young fruit. Based on the results of the analysis parameter testing the t-test, it can be concluded that there is a significant difference in the antioxidant activity of the young and ripe srikaya fruit extract (Annona squamosa L.). The antioxidant activity test of young and ripe Srikaya fruit extract (Annona Squamosa L.) had been carried out by using the FRAP (Ferric Reducing Antioxidant Power) method. This study aims to determine the antioxidant activity of young and ripe srikaya fruit extract using the FRAP method by using qualitative and quantitative method. The research method used was FRAP (Ferric Reducing Antioxidant Power) which was based on a reduction reaction in an acid state towards a yellow Fe3+ (Potassium hexacyanoferat(III)) complex compound to become a bluish-green Fe2+ complex compound due to electron donors from antioxidant compounds. The result of the qualitative analysis of the antioxidant activity of young and ripe srikaya fruit extract was a change in color in the sample extracts of young and ripe Srikaya fruit due to the reduction reaction in an acid state towards the yellow-colored Fe3+ (Potassium hexacyanoferat(III)) complex compound to become a bluish-green Fe2+ complex compound. due to electron donor of antioxidant compounds. Quantitatively, the average antioxidant activity of samples of young and ripe srikaya fruit extract using the FRAP method was respectively 7,448 mgAAE/g extract and 9,351 mgAAE/g extract. The result indicated that the antioxidant activity of ripe srikaya fruit was greater than that of young fruit. Based on the results of the analysis parameter testing the t-test, it can be concluded that there is a significant difference in the antioxidant activity of the young and ripe srikaya fruit extract (Annona squamosa L.).